Transcriptome analysis reveals changes in lignin and flavonoid biosynthesis in Serendipita indica colonized Tartary buckwheat - Wang, Wenjing; Zhong, Shanpu; Tang, Wuyao; Zhou, Xingmei; Li, Shengjie; Ding, Binhan; Wang, Tao; Bu, Tongliang; Tang, Zizhong; Li, Qingfeng (Frontiers in Plant Science, 2025)
IntroductionTartary buckwheat (Fagopyrum tataricum Gaertn.), classified as a food and herbal medicinal crop, offers substantial nutritional benefits but suffers from poor yields and quality. Studies indicate that Serendipita indica positively impacts Tartary buckwheat's yield and quality, yet the underlying processes remain largely unexplored.MethodsThis study aimed to examine the genetic transcript of Tartary buckwheat in both colonized and uncolonized S. indica. ResultsIt was discovered that the pathway for producing phenylpropanoids in Tartary buckwheat, both in colonized and uncolonized S. indica, both in colonized and uncolonized S. indica, was found to be enriched in KEGG (Kyoto Encyclopedia of Genes and Genomes). Genetic expression analysis of lignin and flavonoid biosynthesis pathways in colonized S. indica showed a comparison between lignin biosynthesis pathway genes in colonized S. indica and those in uncolonized S. indica in Tartary buckwheat. Research revealed a decrease in certain genes linked to lignin synthesis and an increase in others associated with flavonoid biosynthesis in both colonized and uncolonized S. indica Tartary buckwheat. Furthermore, research revealed a reduction in lignin levels in Tartary buckwheat stems and seeds both colonized and uncolonized by S. indica, in contrast to an increase in flavonoid levels in leaves and seeds of Tartary buckwheat colonized and uncolonized by the same fungi.DiscussionFindings indicate that the process of synthesizing lignin and flavonoids could offer valuable insights into how S. indica enhances Tartary buckwheat's yield and quality.